An Examination of Adolescents' Knowledge and Attitudes Related to Heart Disease, Nutrition, Physical Activity, and Media Influences and the Adoption of a Healthy Lifestyle - Melissa Schenkman; Randolph Martin; Susan Butler (Georgia Southern University, 2006)
The present pilot study aimed to determine the attitudes, beliefs, behaviors, and degree of knowledge among adolescents related to healthy eating, exercise, heart disease, the influence of television, and possible factors in modifying their attitudes toward adopting a healthy lifestyle. Juniors and seniors from two private high schools (N=62) in metro Atlanta were surveyed. The study was based on the Social Cognitive Theory and the Health Belief Model. The research questions examined the impact of nutrition and heart disease knowledge on physical activity behavior, and the impact of television media exposure on eating habits. A 36-question cross-sectional survey compiled from various sources in the literature and health-related organizations was used to assess the outcomes of interest. Data analysis was conducted using frequencies, descriptive statistics, simple hypothesis tests, and chi square analysis. Those who reported physical activity participation and those who did not, were not found to differ significantly on their composite nutrition and heart disease knowledge score, F(6,55)=.763, p=. 602. In addition, the three groups, reporting different amounts of physical activity participation in hours/week, were not found to differ significantly on their composite nutrition and heart disease knowledge score F (6, 50)=1.628, p=. 159. In terms of television viewing's effect on eating habits, television viewing was not found to play a significant role in the frequency of breakfast food consumption F (3, 57)=2.269, p=. 090; or on how often adolescents ate fast food, F (1, 59)=.025, p=. 875. Yet, the amount of television hours viewed on a typical weekday were significantly related to how often an adolescent thinks about their health when deciding what to eat (X= .008). The 5 groups of amounts of television viewing hours, differed significantly on how often adolescents thought about their health when deciding what to eat, specifically those who thought about their health always and sometimes F (3, 57)=3.241, p=. 029). The Post Hoc test showed a significant difference of .998 hours in the amount of TV watched by those who always think about their health when deciding what to eat (M=2.11 hours/weekday) and those who sometimes think about it (M=3.10 hours/weekday). Suggested primary implications for public health practice include access to school-sponsored or recreational sports teams for all adolescents, nutrition and heart disease education via sports teams, and parental involvement in their adolescent's food choices and health behavior.